2019
DOI: 10.1536/ihj.18-416
|View full text |Cite
|
Sign up to set email alerts
|

Additional Value of Early Repolarization Pattern in Prediction of Obstructive Coronary Artery Disease as Assessed by Coronary Angiography

Abstract: Recent reports show that an early repolarization pattern (ERP) is associated with a higher incidence of sudden cardiac death in patients with obstructive coronary artery disease (CAD). Sporadic case studies have pointed out that ERP might be related to obstructive CAD.In consecutive patients who had undergone coronary angiography, we investigated the relationship between ERP and obstructive CAD by evaluating its association with coronary artery stenosis.The study population consisted of 3785 patients (59.9% me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…Fourth, our previous study and other reports have identified that ERP could be a marker of underlying structural heart diseases (ischemic, cardiomyopathy, etc) and not just a pure electrical phenomenon. 35 , 36 We thus performed sensitivity analyses by excluding subjects with coronary heart disease or chronic heart failure, but the results did not materially change. This might further corroborate our hypothesis that dynamic ERP could be an independent risk factor for cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Fourth, our previous study and other reports have identified that ERP could be a marker of underlying structural heart diseases (ischemic, cardiomyopathy, etc) and not just a pure electrical phenomenon. 35 , 36 We thus performed sensitivity analyses by excluding subjects with coronary heart disease or chronic heart failure, but the results did not materially change. This might further corroborate our hypothesis that dynamic ERP could be an independent risk factor for cardiovascular outcomes.…”
Section: Discussionmentioning
confidence: 99%